Mutations affecting domain V of the 23S rRNA gene in Helicobacter pylori from Cairo, Egypt. (2nd September 2016) - Ghaith, Doaa; Elzahry, Mohammad; Mostafa, Gehan; Mostafa, Sally; Elsherif, Rasha; Ramzy, Iman
Abstract : Background: Clarithromycin is a main component of the recommended first-line triple therapy for Helicobacter pylori in Egypt. We aimed in our study to investigate the prevalence of clarithromycin-resistant H. pylori strains due to the point mutations at domain V of the H. pylori 23S rRNA among the Egyptian population using the polymerase chain reaction/restricted fragment length polymorphism (PCR/RFLP) assay. Methods: Gastric biopsies obtained from 100 dyspeptic patients who consecutively attended at Cairo University Hospital during the period from January to November 2013 were subjected to PCR/RFLP in order to detect the point mutations at domain V of the H. pylori 23S rRNA associated with clarithromycin resistance. The PCR amplicon of the 23S H. pylori rRNA is restricted with M boII for detection of A2142G mutation and with B saI for A2143G mutation. Results: The prevalence of H. pylori infection among 100 patients was 70%; clarithromycin resistance was detected in 39/70 (57.7%) of positive H. pylori isolates. Occurrence of 23S rRNA A2142G mutations resulted in two DNA fragments (418 and 350 bp) by PCR-RFLP; on the other hand, no A2143G mutations were detected. Conclusions: The high prevalence of clarithromycin resistance (57.7%) caused by A2142G mutations at domain V of the H. pylori 23S rRNA may mandate changing of the standard clarithromycin-containing triple therapy. The PCR/RFLP assay was a rapid and accurate method for molecular detection of H. pylori infection in addition to determination of different nucleotide mutations causing clarithromycin resistance.